S100A9 Activates the Immunosuppressive Switch Through the PI3K/Akt Pathway to Maintain the Immune Suppression Function of Testicular Macrophages - Fan, Zun Pan; Peng, Mei Lin; Chen, Yuan Yao; Xia, Yu Ze; Liu, Chun Yan; Zhao, Kai; Zhang, Hui Ping (Frontiers in Immunology, 2021)
Macrophages are functionally plastic and can thus play different roles in various microenvironments. Testis is an immune privileged organ, and testicular macrophages (TMs) show special immunosuppressive phenotype and low response to various inflammatory stimuli. However, the underlying mechanism to maintain the immunosuppressive function of TMs remains unclear. S100A9, a small molecular Ca2+ binding protein, is associated with the immunosuppressive function of macrophages. However, no related research is available about S100A9 in mouse testis. In the present study, we explored the role of S100A9 in TMs. We found that S100A9 was expressed in TMs from postnatal to adulthood and contributed to maintaining the immunosuppressive phenotype of TMs, which is associated with the activation of PI3K/Akt pathway. S100A9 treatment promotes the polarization of bone marrow-derived macrophages from M0 to M2 in vitro. S100A9 was significantly increased in TMs following UPEC-infection and elevated S100A9 contributed to maintain the M2 polarization of TMs. Treatment with S100A9 and PI3K inhibitor decreased the proportion of M2-type TMs in control and UPEC-infected mouse. Our findings reveal a crucial role of S100A9 in maintaining the immunosuppressive function of TMs through the activation of PI3K/Akt pathway, and provide a reference for further understanding the mechanism of immunosuppressive function of TMs.